Owlknight - Lackey, Mercedes (Lackey, Mercedes. Darian's tale., 1999)
Two years after his parents disappearance, Darian has sought refuge and training from the mysterious Hawkbrothers. Now he has opened his heart to a beautiful young healer. Finally Darian has found peace and acceptance in his life. That is, until he learns that his parents are still alive-and trapped behind enemy borders....